First report of extended-spectrum beta lactamase (ESBL) and carbapenemase-producing MDR Klebsiella pneumoniae from Fuchka - Bushra Benta Rahman Prapti; Md. Tanjir Ahmmed; Aminur Rahman; Chandra Shaker Chouhan; Mahbubul Pratik Siddique (PLoS ONE, 2026)
Extended-spectrum beta-lactamase (ESBL) and Carbapenemase-producing Gram-negative bacteria, particularly Klebsiella pneumoniae (ESBL-KP and CP-KP), in the food supply chain, poses a significant public health threat. Ready to eat (RTE) street foods, especially fuchka, a highly popular snack in Bangladesh, India and Southeast Asia, represents a critical breach in food safety. This study investigated the multidrug resistance (MDR) patterns of K. pneumoniae isolated from fuchka with an emphasis on phenotypic and genotypic detection of ESBL-KP and CP-KP. A total of 60 samples were collected from 15 fuchka selling points. K. pneumoniae was isolated and identified via staining, cultural methods, PCR and MALDI-ToF-MS biotyper. Antibiotic susceptibility test (AST) was accomplished using disk diffusion method, phenotypic ESBL producers was detected by combined disk test (CDT) and PCR was used to detect resistance determinant. Thirty K. pneumoniae isolates were confirmed by PCR and MALDI-ToF-MS. All showed resistance to amoxicillin and cefuroxime (100%), while most were sensitive to cefepime (96.7%), norfloxacin (96.7%), imipenem (93.3%) and meropenem (83.3%). All the isolates were MDR, with multiple-antibiotic resistance (MAR) index values ranged from 0.28 to 0.64. CDT confirmed 28 ESBL producers. Among ESBL-producing genes bla TEM, was most prevalent (64%), followed by bla SHV, bla OXA-1, bla CTX-M1, bla CTX-M3. Among carbapenem-resistant genes, bla BIC was most common (46%), while bla VIM was absent. Moreover, other resistance determinants ( aad A1, aac 3IV was most prevalent (40%) but aad A1, qnr A were not detected. The presence of multidrug-resistant, ESBL- and carbapenemase-producing K. pneumoniae in fuchka represents a critical threat to public health.